PENGARUH TEKANAN WAKTU (TIME PRESSURE) DAN DUKUNGAN ORGANISASI (PERCEIVED ORGANIZATIONAL SUPPORT) TERHADAP KUALITAS AUDIT (AUDIT QUALITY) DENGAN STRESS KERJA (JOB STRESS) SEBAGAI VARIABEL MEDIASI PADA PEGAWAI SUBUNSUR AUDIT KANWIL DIREKTORAT JENDERAL BEA DAN CUKAI JAWA TIMUR I - Yazid, Zulfadli; Rahayu, Sri; Fitrianty, Rifda (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to analyze the effects of time pressure and perceived organizational support on audit quality, with job stress as a mediating variable among employees of the Audit Subunit at customs and excise regional office I of east java. This study employed a quantitative approach using a survey method. The population and sample consisted of 41 employees selected through saturated sampling. Data were collected using a Likert-scale questionnaire and analyzed using Partial Least Squares Structural Equation Modeling with SmartPLS. Hypothesis testing was conducted through bootstrapping with 500 subsamples. The results show that time pressure has a positive and significant effect on job stress, while perceived organizational support has a negative and significant effect on job stress. Job stress has a negative and significant effect on audit quality. Time pressure and perceived organizational support do not have significant direct effects on audit quality. Job stress mediates the effect of time pressure on audit quality but does not mediate the effect of perceived organizational support on audit quality. These findings indicate that managing time pressure and job stress is essential for maintaining audit quality.